Adverse effects related to frequent hand hygiene during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
Occupational dermatosis, have raised extensively due hand hygiene with soap or alcohol-based sanitizers in the context of COVID-19 pandemic, once these products break the skin. In this perspective, this study aims to identify the most important skin injuries related to hand hygiene amongst health workers during the COVID-19 pandemic. An integrative review has been carried on through a search strategy involving terms and key words in three databases (Medline, Scopus and Embase). An unbiased evaluator selected observational studies that analyzed the outcomes of interest involving individuals between 30 and 49 years old, published in 2020 and 2021, with restriction of language (only English). Initially, 290 articles have been found, but only 15 met the inclusion criteria. 14 of them were cross-sectional studies and 1 was a prospective study. 70% (11 studies) identified Irritant Contact Dermatitis as the main occupational dermatosis on account of excessive hand hygiene. Dryness, desquamation and erythema were the main skin lesions found in 12 studies (80%). With regard to risk , three articles (20%) mention that the frequency of more than 20 times of hand wash as an important risk factor. Moreover, 9 studies observed that the hydration of the skin hand as a protective factor. Four articles (25%) pointed that alcohol-based sanitizers are less aggressive to the skin, when compared to hand wash with soap and water. After the review, the results  have found that Irritant Contact Dermatitis is the most important skin injury that affects health care workers during the COVID-19 pandemic.